2020
DOI: 10.1111/ddi.13048
|View full text |Cite
|
Sign up to set email alerts
|

Predicted distributions of avian specialists: A framework for conservation of endangered forests under future climates

Abstract: Aim: Forested regions are of global importance for a multitude of ecosystem functions and services and are critical for biodiversity. Anthropogenic climate-change compounds negative effects of land-use change on forest persistence and forestdependent biodiversity. Habitat loss and climate change have an additive effect and drive species' extinctions in similar ways, resulting in a homogenization of biodiversity. Connectivity is key in conservation planning for mitigating climate change effects and facilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…Stronger performance of the LCP models of native forest and dense thicket configuration over respective IBR models for P. stellata (Figure 7e ), as well as B. capensis and C. dichroa (Tables 2 and 3 ) demonstrate the potential utility of conservation corridors in the Eastern Cape and southern KwaZulu‐Natal to preserve genetic integrity within regional Afromontane forest birds. Such corridors should promote resilience anthropogenic climate change, as recommended by Colyn et al ( 2020 ). The highest priority forests for conservation are the scarp forests present along the Wild Coast, as well the eastern Amatole Afromontane forests, and Afromontane (eastern mistbelt) forests in southern KwaZulu‐Natal.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger performance of the LCP models of native forest and dense thicket configuration over respective IBR models for P. stellata (Figure 7e ), as well as B. capensis and C. dichroa (Tables 2 and 3 ) demonstrate the potential utility of conservation corridors in the Eastern Cape and southern KwaZulu‐Natal to preserve genetic integrity within regional Afromontane forest birds. Such corridors should promote resilience anthropogenic climate change, as recommended by Colyn et al ( 2020 ). The highest priority forests for conservation are the scarp forests present along the Wild Coast, as well the eastern Amatole Afromontane forests, and Afromontane (eastern mistbelt) forests in southern KwaZulu‐Natal.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to early work on plains spotted skunks that revealed high densities in highly anthropogenic agricultural landscapes (Crabb 1948), most recent researchers have reported that both plains and eastern spotted skunks select for denser forests within large forest stands at the microhabitat scale (Hackett 2008;Lesmeister et al 2008Lesmeister et al , 2013Thorne et al 2017). We continue to lack a clear understanding of how habitat fragmentation at the landscape level could limit dispersal, which could affect metapopulation dynamics and population persistence across the range (Ims and Andreassen 2002, Sgro et al 2011, Colyn et al 2019. Despite high to medium-high predicted presence of the species in large portions of northern, western, and southern Arkansas and southern Missouri predicted by our models, there are significant spatial gaps predicted by our models that suggest remaining populations could be isolated.…”
Section: Discussionmentioning
confidence: 94%
“…Climatic resilience of Afromontane forests within the MPA Hotspot, however, may rely upon elevational shifts of forests (see Figure 4). Given that anthropogenic landscape transformation impedes the expansion of forest tree communities (Botzat et al, 2015; Ivory et al, 2019), wildlife corridors may be necessary to mitigate the impact of anthropogenic climate change on sensitive forest taxa (Colyn et al, 2020; Mulvaney et al, 2021). Our palaeodistributional modelling demonstrates the utility that such corridors served in promoting forest connectivity under different climatic regimes (Figure 4), which may be of conservation importance in the Anthropocene.…”
Section: Discussionmentioning
confidence: 99%